Efektivitas Bauran Komunikasi Pemasaran Taman Wisata Alam Pananjung, Kecamatan Pangandaran, Kabupaten Pangandaran, Jawa Barat - Fenny Istiana; Sutisna Riyanto (Institut Pertanian Bogor, 2018)
The success of ecotourism in area depends on how big and incessant the marketing communication activities undertaken by the local government and related parties. Effective marketing communication is important aspect of the overall marketing mission as well as the determinant of successfull marketing. The purpose of this research is to analyze the form of marketing communication mix, to analyze the effectiveness of marketing communication mix on cognitive, affective, and conative aspects, to analyze the relationship between visitor characteristics and marketing communication mix with marketing communication effectivity. The research method used is quantitative research supported by qualitative data. The result of the research shows that there is a significant correlation between the visitor characteristic in the age with the effectiveness of the marketing communication mix on the affective aspect and visitor characteristics on income level with the effectiveness of the marketing communication mix on the affective and conative aspects.